2012
DOI: 10.1371/journal.pone.0043660
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosoglutathione Acts as a Small Molecule Modulator of Human Fibrin Clot Architecture

Abstract: BackgroundAltered fibrin clot architecture is increasingly associated with cardiovascular diseases; yet, little is known about how fibrin networks are affected by small molecules that alter fibrinogen structure. Based on previous evidence that S-nitrosoglutathione (GSNO) alters fibrinogen secondary structure and fibrin polymerization kinetics, we hypothesized that GSNO would alter fibrin microstructure.Methodology/Principal FindingsAccordingly, we treated human platelet-poor plasma with GSNO (0.01–3.75 mM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…They demonstrated that contraction of the muscle resulted in a tenfold increase in RBC velocity without an increase in perfused capillary density . Although our preparation of the EDL for transillumination requires tying a suture around the distal tendon and cutting the tendon between the suture and its attachment, the muscle maintains a stable microvascular perfusion with resting RBC velocities for up to 5‐6 hours similar to those reported by Tyml . Two independent research groups have also shown that exteriorization does not alter muscle flow .…”
Section: Discussionmentioning
confidence: 81%
“…They demonstrated that contraction of the muscle resulted in a tenfold increase in RBC velocity without an increase in perfused capillary density . Although our preparation of the EDL for transillumination requires tying a suture around the distal tendon and cutting the tendon between the suture and its attachment, the muscle maintains a stable microvascular perfusion with resting RBC velocities for up to 5‐6 hours similar to those reported by Tyml . Two independent research groups have also shown that exteriorization does not alter muscle flow .…”
Section: Discussionmentioning
confidence: 81%
“…Additional studies have investigated the role of GSNO treatment on fibrin clot structure. Fiber density decreased and fiber diameter increased following GSNO treatment of PPP [82]. …”
Section: Oxidative Modifications Of Fibrinogenmentioning
confidence: 99%
“…Fibrinogen interacts with tissue factors and cytokines, such as fibroblast growth factor-2, vascular endothelial growth factor and interleukin-1β [3]. Hyaluronic acid and S-nitrosoglutathione are able to bind to fibrinogen and fibrin causing modulation of their functions [5,6].…”
Section: Introductionmentioning
confidence: 99%